Measuring National Culture Impact (NCI) At An Individual Level: A Conceptual Model For Capturing The NCI On Knowledge Sharing Via Video-Conferencing - Alkhaldi, Ayman N.; Yusof, Zawiyah M.; Ab Aziz, Mohammad. J. (Journal of Knowledge Management Practice, 2011)
Knowledge is deemed necessary in giving competitive advantages. As globalization comes into view, technologies are unavoidable in enabling interactions between virtual teams, across cultures, in materialising the sharing of knowledge. This paper seeks to investigate the impact of national culture, by means of video conferencing, on knowledge sharing. Existing models that capture national cultural impact are lacking, in that they only focus on general information technology acceptance, without any particular medium other than measuring national culture at a national level. These authors were carried out a review on previous work; and examine cultural and technology acceptance theories before proposing a conceptual model. Studies on the cultural dimension yielded contradicting results. It is important to measure national cultural value at an individual level, as the results are more accurate than measuring at other levels, such as organizational or national. The proposed model will be able to address articulated views on the impact of national culture through video conferencing, on the endeavour of knowledge sharing.